Surrogate Modelling of Propeller Noise in Unsteady Load Conditions - Neto, Pedro Matos (2021)
The recent developments in electric technologies have been a catalyst to the electrification of air transport which typically requires the usage of propellers, known to produce high levels of noise. When coupled with tightening noise regulations and the possibility of operation near urban areas, an interest to study propeller noise arises. This dissertation presents the formulation and implementation of a numerical propeller noise analysis tool. The tool is capable of estimating the noise produced by a propeller under different inflow conditions and is designed to be used in propeller geometry optimisation problems where the inflow conditions, observer position and velocity and the range of propeller geometric characteristics are specified. The code uses Latin Hypercube Sampling to select a space-filling set of propellers; Then, the overall sound pressure level (OASPL) for these samples is calculated using a formulation of the Ffowcs-Williams and Hawkings (FW-H) equation with loading data from a modified Blade Element Momentum (BEM) theory; A Kriging model is then produced and made available to the user for direct analysis or further implementation in optimisation problems. Validation cases are presented for all modules of the tool and a study case with a propeller operating in a push configuration is analysed. The different modules of the model were validated against experimental and numerical data from the literature with promising results. In addition, a case study was performed where a propeller operates in the wake of a wing. The results show that there is a clear difference in noise produced under unsteady load conditions. In addition, it is noted that blade chord, radius, incidence and count can be tuned to minimise noise.